Design and Simulation of a Highly Reliable Modular High-Power Current Source - Qing Zhou; Yuelei Xu; Xin Qi; Zhaoxiang Zhang (Energies, 2022)
Currently, modularization, low complexity, and high performance are the three directions that high-power power supplies are gradually moving toward. Under the premise of determining the objective conditions such as operating environment and material technology, a significant task in power supply reliability design is to optimize the power supply’s structure, topology, and mode of operation. In this paper, we analyze the reliability design of parallel module redundancy in detail and design the overall structure of the power supply. To further improve the reliability of the power supply, methods for power reliability design at the leg level and component level are proposed. This paper verifies the correctness of the design through simulation and develops a N + 1 modular redundant power supply according to the design scheme. The simulation experiment verifies the consistency of the design scheme and parameters.